Heart failure and anemia in patients with acute myocardial infarction - T. Yu. Kalyuta; R. E. Lubeznov; O. V. Orlikova; Yu. G. Schwartz (Российский кардиологический журнал)
In-hospital management of myocardial infarction was analyzed for 150 patients (54 women). Mean age was 59, 6+1, 1 years for men, and 69, 2+1, 1 years for women. All participants underwent thrombolysis. Patients with severe associated pathology and hemorrhage in anamnesis were excluded from the study. Red blood cell count and hemoglobin (Hb) level in capillary blood were measured at admission. Death, acute heart failure, left ventricular dysfunction (by echocardiography criteria) were registered. At discharge, anemia was observed in 42 participants. Individuals, who died from cardiogenic shock, had lowest Hb levels (128, 6 ± 4, 1 g/l), comparing to participants, who died from other causes (135, 3 ± 5, 7 g/l), and survivors (133, 1+1, 2 g/l). Anemia was an independent predictor of middle-term in-hospital mortality (odds ratio 4, 7; p < 0, 05). Predischarge ejection fraction was directly linked to Hb level at admission (t = 2, 34; p < 0, 05).